PREVALENCE AND INDIVIDUAL FACTORS ASSOCIATED WITH DYSMENORRHEA AMONG MEDICAL STUDENTS AT FORT PORTAL COLLEGE OF HEALTH SCIENCES, WESTERN UGANDA – A CROSS-SECTIONAL STUDY. - Ignatius , Diplock; Mukirya , Namaasa Aeron (Student's Journal of Health Research Africa, 2025)
Introduction Dysmenorrhea is a common complaint among women of reproductive age and it affects academic performance among students. This study aimed to determine the prevalence and individual factors associated with dysmenorrhea among female medical students at Fort Portal College of Health Sciences, western Uganda. Methods A cross-sectional study was conducted on 280 participants from the five training programs offered at the college. Participants were selected using stratified random sampling. A self-administered questionnaire was used to collect data on socio-demographic characteristics, prevalence, and individual factors associated with dysmenorrhea. Data was analyzed in SPSS v.21, using mean, frequencies, percentages, chi-square, and logistic regression. Ethical and administrative approvals were sought for the College Research and Scientific Committee and administration, respectively and participants provided written informed consent. Results Data was collected from 280 participants with a mean age of 23.26 years (S=3.58). The prevalence of dysmenorrhea among participants was 94.26%; and participants’ age (aOR=2.74; 95% CI: 0.36 – 20.86; p-value = 0.331), duration of menstrual flow (aOR=2.36; 95% CI: 0.66 – 8.39; p-value = 0.184), regular physical exercises (aOR=1.61; 95% CI: 0.85 – 3.05; p-value = 0.142), and daily water consumption (aOR=3.45; 95% CI: 1.15 – 10.37; p-value = 0.068), were not associated with dysmenorrhea. Conclusion The prevalence of dysmenorrhea among female medical students is high and is not associated with individual factors like; age, duration of menstrual flow, physical exercises, or daily water consumption. Recommendation Additional studies are needed to examine the aetiology of dysmenorrhea and inform the development of effective prevention and control strategies.